The influence of beliefs and anxiety in using artificial intelligence towards readiness to change with high performance work systems as a moderating variable - Novita, Rahmi; Sulastri, Sulastri (Universitas Negeri Padang, 2023)
This research aims to examine the influence of: (1) Beliefs in Using AI on Change Readiness to Adopt AI among PT SP Manufacturing employees . ( 2) Anxiety in Using AI on Change Readiness to Adopt AI among PT SP Manufacturing employees . ( 3) HPWS moderates the relationship between Anxiety in Using AI and Change Readiness to adopt AI in PT SP Manufacturing employees . This research uses a causative design. The population of this study was 133 employees of PT SP Manufacturing who use AI-based products and a sample of 100 people was taken using clustered simple random sampling. Data collection used a questionnaire with a Likert Scale. The results of data management show that: (1) Beliefs in Using AI has a positive effect on Readiness to Change to Adopt AI. (2) Anxiety in Using AI has a negative effect on Change Readiness to Adopt AI. (3) HPWS significantly moderates the relationship between Anxiety in Using AI and Readiness to Change to Adopt AI. HPWS weakens this relationship.